PENGEMBANGAN MODUL PEMBELAJARAN FISIKA TERINTEGRASI ISLAM SAINS PADA MADRASAH ALIYAH - Ismayani Ismayani; Dewi Sartika; Nursakinah Annisa Lutfin (Karst: Jurnal Pendidikan Fisika dan Terapannya, 2024)
This research aims to develop a physics learning module integrated with the concept of Islamic-science at Madrasah Aliyah which is sought to meet the criteria of valid, practical and effective in the learning process. This module is designed by integrating Al-Quran verses and hadith on each subject matter of physics discussed. This research uses a Research & Development approach with the ADDIE model which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The research was conducted at MAN 1 Majene, West Sulawesi. Data were collected through questionnaires and learning outcome tests. The results of the development of Islamic-science integrated physics learning modules are (1) declared valid with an average score of 3.05 from 3 expert validators; (2) declared practical by getting positive response scores from students during the learning process in terms of its use; (3) analysis of learning outcomes from all three aspects (cognitive, psychomotor, affective) is classified as effective with a good category. Based on these results, the physics learning module integrated with Islam-science meets the criteria of valid, practical, and effective.